Help on the road: Effects of vehicle manual consultation in driving performance across modalities. Issue 73 (January 2015) - Alvarez, Ignacio; Alnizami, Hanan; Dunbar, Jerone; Jackson, France; Gilbert, Juan E.
Abstract: The growing advancements of in-vehicle electronics and the intrusion of consumer electronics in the vehicle cockpit have increased the complexity of in-car experiences. Therefore, vehicle manuals are needed, now more than ever, to provide information and guidance. Automakers have extended user assistance through multimedia, integrated manuals, online services and telephonic assistance. However, no driver-centric interfaces have been created to provide vehicle documentation assistance effectively. Drivers are expected to interrupt the driving experience in order to find vehicle information in a paper manual. This paper compares the effects on driving performance and cognitive load when consulting a manual in a simulated driving environment through various conditions. These conditions consist of interacting with a voice activated vehicle manual called the Voice User Help, an on-board multimedia manual, a passenger, and a call center. Results suggest that any kind of interaction to access information while driving has an impact on the driver׳s attention based on a decrease in driving performance and increase of cognitive load. However, amongst all modalities, voice interfaces seem to be the better option for consulting information while driving. Also, and under some circumstances, interaction with a conversational manual system appears to be safer than human-to-human communication. Highlights: Voice impact less driver performance than interactions with manual inputs. In-vehicle conversations improve driver performance vs. "out-of-the-vehicle". Lane-keeping while using VUH is less distractive than interactions with humans. VUH has short learning curve, high user acceptance and low driver performance impact. Road-aware voice applications can be less distractive than passenger interactions.